Preparation method of charcoal granules capable of repairing water body polluted by multiple heavy metals

By preparing magnetic biochar particles loaded with PNIPAM, the problems of low treatment efficiency, difficulty in recycling and low material regeneration efficiency in the prior art are solved, and the effects of efficient removal, easy recycling and recycling are achieved.

CN119838567APending Publication Date: 2025-04-18WUHAN WONONG FERTILIZER
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510240983.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-03
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The prior art has poor efficiency in removing a variety of heavy metal contaminated water bodies, is difficult to recover, and is low in material regeneration efficiency, resulting in environmental pollution and material performance degradation.

Method used

By preparing a magnetic biochar particle loaded with PNIPAM, using iron salt impregnation, pyrolysis, CO2 activation, TiO2 co-precipitation loading and surface activation, a composite material with magnetic and temperature responsive characteristics is formed, achieving efficient removal of heavy metals, easy recycling and recycling.

Benefits of technology

The efficient removal of various heavy metals was achieved, with a recovery rate of up to 97.6%. The adsorption capacity of the material remained above 80% after three cycles, avoiding the damage to the material structure by traditional strong acid and strong alkali desorption, and achieving green circulation treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005294128290000061
    Figure BDA0005294128290000061
  • Figure BDA0005294128290000071
    Figure BDA0005294128290000071
  • Figure BDA0005294128290000072
    Figure BDA0005294128290000072
Patent Text Reader

Abstract

The invention relates to a preparation method of biochar particles capable of repairing a water body polluted by multiple heavy metals. The preparation method comprises the following steps of biomass pretreatment, ferric salt impregnation, pyrolysis, CO2 activation, TiO2 coprecipitation loading, surface activation, PNIPAM graft polymerization, granulation, screening and drying, recovery after material use, temperature control desorption and reutilization of the biochar particles. The method has the following advantages and effects that various heavy metals in the polluted water body can be efficiently removed, and the method is easy to recycle and can be recycled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of environmental restoration materials, and in particular to a method for preparing biochar particles capable of repairing water bodies polluted by multiple heavy metals. Background Art

[0002] Heavy metals such as cadmium, arsenic, chromium, and nickel in sewage can harm human health through the food chain and drinking water due to their toxicity and bioaccumulation. Heavy metal pollution in water bodies has become a global environmental problem, and its governance faces three major challenges:

[0003] 1. Existing treatment technologies are not ideal for the synergistic removal of multiple heavy metals. Biochar is a relatively economical carbon skeleton material that can effectively remove cationic heavy metals, including Cd(II), Pb(II), Cu(II) and Zn(II), due to its large specific surface area, high pH value, rich surface charge, high porosity and abundant oxygen-containing functional groups. However, due to the opposite zeta potential and pH dependence of cations and anions, biochar cannot remove As. At the same time, the adsorption effect of many heavy metals (Ni(II), Cr(VI), etc.) is also not ideal.

[0004] 2. Difficulty in recycling processed materials. Currently, the commonly used powdered biochar has good dispersibility but poor physical strength, making it difficult to recycle and causing secondary pollution; while granular biochar is easy to recycle but has a small specific surface area and poor adsorption performance, which seriously limits its practical application.

[0005] 3. Low material regeneration efficiency. Existing heavy metal adsorption materials often require the use of strong acid, strong alkali and other chemical reagents during the desorption process, which not only pollutes the environment, but also destroys the material structure, resulting in a decrease in recycling performance.

[0006] In response to the above problems, there is an urgent need to develop a new type of water treatment material with the following characteristics: efficient removal of multiple heavy metals, easy recycling, controllable desorption and recycling. Summary of the invention

[0007] The present invention aims to provide a method for preparing biochar particles that can repair water bodies polluted by various heavy metals. The method can not only efficiently remove various heavy metals in the polluted water bodies, but also be easy to recycle and can be recycled.

[0008] The above technical objectives of the present invention are achieved through the following technical solutions: A method for preparing biochar particles that can repair water bodies polluted by multiple heavy metals, comprising the following steps:

[0009] (1) Biomass pretreatment: The recycled agricultural waste is washed to remove dirt and impurities, then cut into small pieces of 1-2 cm, placed in an oven and dried at 60°C to constant weight to obtain dry biomass;

[0010] (2) Iron salt impregnation: Weigh 1 kg of the dried biomass obtained in step (1) and immerse it in 20 liters of 0.1 mol / L -1 Fe 3+ The solution was then added with oxalic acid dihydrate and then 1 mol L -1 The pH value was adjusted to 6-7 by using NaOH solution, and then the mixture was stirred continuously for 3 h in a water bath at 90 °C, covered with plastic wrap, reacted for 24 h, and the solid product was collected by vacuum filtration and washed with deionized water until the filtrate was neutral. Finally, the solid product was vacuum dried at 50 °C for 24 h to obtain dry iron-loaded biomass.

[0011] (3) Pyrolysis: The dried iron-loaded biomass obtained in step (2) is placed in a quartz crucible of a microwave pyrolysis furnace, evenly spread, and high-purity nitrogen is introduced at the same time. The temperature is then raised to 400°C at 20°C min-1, and the pyrolysis is maintained at 400°C for 120 min. The temperature is then naturally lowered to obtain a pyrolysis product. The obtained biochar is then ground and passed through a 100-mesh sieve to obtain a uniform biochar powder.

[0012] (4) CO2 activation: The biochar powder obtained in step (3) was placed in a quartz boat in a tube furnace, evenly spread, and then high-purity carbon dioxide gas (flow rate of 150 mL min) was introduced. -1 ), 5℃min -1 The heating rate was raised to 800°C, and the temperature was maintained for 1 hour for activation treatment, and activated magnetic biochar was obtained after cooling;

[0013] (5) TiO2 co-precipitation loading: 1 kg of activated magnetic biochar obtained in step (4) was dispersed in 10 L of deionized water, ultrasonically stirred for 30 minutes, and then 1 L of 0.5 mol L -1 TiCl4 solution, continue stirring for 1 hour, then slowly add 1 mol L -1 The pH was adjusted to 7 with ammonia water, and the mixture was stirred for 2 hours to precipitate the TiO2 precursor on the surface of the biochar. The solid product was then vacuum filtered and washed with deionized water until neutral. Finally, the solid product was dried at 100 °C for 12 hours and calcined at 400 °C for 2 hours to obtain magnetic biochar loaded with titanium dioxide.

[0014] (6) Surface activation: 1 kg of the titanium dioxide-loaded magnetic biochar obtained in step (5) was added to 10 L of a 10% ammonium persulfate solution, and stirred in a 60° C. water bath for 2 hours. After the reaction was completed, the mixture was filtered and washed with deionized water until the filtrate was neutral. The obtained product was then vacuum dried at 20° C. for 12 hours to obtain surface-activated magnetic biochar.

[0015] (7) Graft polymerization of PNIPAM: 1 kg of surface-activated magnetic biochar was dispersed in 10 L of deionized water and ultrasonically stirred for 30 min. Then, under nitrogen protection, an initiator was added to the solution and stirred evenly. The mixed solution was then heated to 70 °C and reacted under nitrogen protection for 6 h. After the reaction was completed, it was cooled to room temperature, filtered, and washed with deionized water until no monomer remained. The product was vacuum dried at 20 °C for 12 h to obtain magnetic biochar loaded with PNIPAM.

[0016] (8) Granulation: The PNIPAM-loaded magnetic biochar obtained in step (7) was mixed with ordinary Portland cement in a mass ratio of 1:5, introduced into a disc granulator, started the granulator and set the speed to 20 rpm, and a small amount of distilled water was sprayed while rotating the granulator to gradually form wet granules. The granulation was continued for 3-6 minutes until the granules were formed and reached the desired particle size;

[0017] (9) Screening and drying: The granulated product is passed through 4 mm and 6 mm sieves to screen out biochar particles with a particle size between 4 mm and 6 mm. The screened biochar particles are naturally air-dried at room temperature for 48 hours. After they are hardened and dried, their quality is monitored to ensure that the required compressive strength and physical properties are achieved, and biochar particles that can repair water bodies contaminated by various heavy metals are obtained;

[0018] (10) Recovery of materials after use: Using magnetic separation or screening methods, biochar particles adsorbing heavy metals are recovered from treated water bodies;

[0019] (11) Temperature-controlled desorption: The recovered biochar particles are placed at an appropriate desorption temperature and treated under stirring conditions for 2 hours. After the desorption is completed, the biochar particles and the desorption liquid are separated by filtration;

[0020] (12) Recycling of biochar particles: The desorbed biochar particles were washed with deionized water until neutral, and vacuum dried at 50°C for 12 hours to obtain dried biochar particles.

[0021] As a further configuration of the present invention, in step (2), the amount of oxalic acid dihydrate is Fe 3+ 50% of the molar amount.

[0022] As a further configuration of the present invention, in step (7), the initiator is a mixture of N-isopropylacrylamide monomer and ammonium persulfate, wherein the added amount of N-isopropylacrylamide monomer is 2 kg, and the added amount of ammonium persulfate is 0.1 kg.

[0023] As a further configuration of the present invention, the magnetic separation in step (10) can utilize the magnetism of biochar to quickly separate particles from the water body; screening is suitable for treating larger water bodies or flowing water bodies.

[0024] As a further configuration of the present invention, the decomposition temperature is 40-60°C.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] 1. The present invention innovatively designs a multifunctional composite material structure, forms a magnetic core through iron salt impregnation and pyrolysis, realizes rapid magnetic separation and recovery of materials, and solves the problem of difficult recovery of traditional powdered biochar; by introducing a TiO2 co-precipitation loading layer, the removal efficiency of anionic heavy metals such as arsenic is significantly improved; for the first time, N-isopropylacrylamide (PNIPAM) thermosensitive polymer is grafted onto the biochar surface, realizing temperature-responsive controllable desorption of heavy metals, avoiding the destruction of the material structure by traditional strong acid and strong base desorption.

[0027] 2. The present invention has developed an advanced and efficient preparation process, using agricultural waste (such as straw) as raw materials, realizing waste resource utilization and significantly reducing the preparation cost; innovatively using microwave pyrolysis technology, which saves 30-50% energy compared to traditional muffle furnace pyrolysis, while ensuring that the product pore structure is more uniform and developed; through CO2 activation treatment, the specific surface area of ​​the material is further increased; and a surface gradient modification process is designed to achieve precise control of the magnetic core-TiO2 layer-PNIPAM layer.

[0028] 3. The present invention prepares magnetic biochar loaded with PNIPAM. First, free radical initiation sites are introduced on the surface of biochar by adding ammonium persulfate (APS) solution. Then, N-isopropylacrylamide (NIPAM) monomer and ammonium persulfate (APS) are added as initiators to allow NIPAM to undergo free radical polymerization on the surface of biochar to form a PNIPAM grafted layer. The PNIPAM grafted layer is loaded on the magnetic biochar to form a temperature-responsive polymer, so that the magnetic biochar loaded with PNIPAM can change its hydrophilicity and hydrophobicity when the temperature changes, thereby changing the adsorption and desorption of heavy metal ions by the biochar. When treating polluted water bodies, the water temperature It is usually lower than the phase transition temperature of PNIPAM. At this time, PNIPAM is hydrophilic, which enables the biochar material to adsorb various heavy metal ions. When the polluted water body is treated, the biochar particles are recovered and placed in water above the phase transition temperature of PNIPAM (40-60°C) (PNIPAM phase transition temperature LCST, about 32°C). At this time, PNIPAM is hydrophobic, and the adsorbed heavy metal ions are easily desorbed into the solution. After filtering and drying, dry biochar particles can be obtained. The dry biochar particles can be used again for the repair of heavy metal polluted water bodies, realizing recycling, thereby realizing the recycling and reuse of biochar.

[0029] 4. The material prepared by the present invention exhibits excellent intelligent processing performance. At room temperature (lower than the LCST of PNIPAM 32°C), the material exhibits excellent multi-metal synergistic removal ability for Pb 2+ , Cu 2+ 、Zn 2+ 、Cd 2+ The removal rate of As 3+ 、As 5+ The removal rate reaches over 98%; when the temperature rises to 40-60℃, PNIPAM undergoes a phase change, triggering rapid desorption of heavy metals, and the desorption rate can reach over 85%; the separation and recovery efficiency is as high as 97.6%, which is much better than traditional biochar separation.

[0030] 5. The present invention has established an efficient recycling system. After three cycles of use, the adsorption capacity of most heavy metals remains above 80% of the initial value, and the recovery rate remains above 94.9%, proving the excellent mechanical stability of the material. The entire process only requires temperature control and simple water washing, without the need for additional chemical reagents, achieving true green recycling treatment. Compared with traditional technologies, the present invention not only improves processing efficiency and reduces operating costs, but also achieves sustainable utilization of materials, with significant environmental and economic benefits. DETAILED DESCRIPTION

[0031] The technical solutions in the embodiments are described clearly and completely below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] 1. Preparation of test materials

[0033] 1. Preparation steps of the experimental group (SCBT@PNIPAM):

[0034] (1) Biomass pretreatment: The recycled agricultural waste is washed to remove dirt and impurities, then cut into small pieces of 1-2 cm, placed in an oven and dried at 60°C to constant weight to obtain dry biomass;

[0035] (2) Iron salt impregnation: Weigh 1 kg of the dried biomass obtained in step (1) and immerse it in 20 liters of 0.1 mol / L -1 Fe 3+ The solution was then added with oxalic acid dihydrate (the amount of oxalic acid dihydrate was 50% of the molar amount of Fe3+), and then 1 mol L -1The pH value was adjusted to 6-7 by using NaOH solution, and then the mixture was stirred continuously for 3 h in a water bath at 90 °C, covered with plastic wrap, reacted for 24 h, and the solid product was collected by vacuum filtration and washed with deionized water until the filtrate was neutral. Finally, the solid product was vacuum dried at 50 °C for 24 h to obtain dry iron-loaded biomass.

[0036] (3) Pyrolysis: The dried iron-loaded biomass obtained in step (2) is placed in a quartz crucible of a microwave pyrolysis furnace, evenly spread, and high-purity nitrogen is introduced at the same time. The temperature is then raised to 400°C at 20°C min-1, and the pyrolysis is maintained at 400°C for 120 min. The temperature is then naturally lowered to obtain a pyrolysis product. The obtained biochar is then ground and passed through a 100-mesh sieve to obtain a uniform biochar powder.

[0037] (4) CO2 activation: The biochar powder obtained in step (3) was placed in a quartz boat in a tube furnace, evenly spread, and then high-purity carbon dioxide gas (flow rate of 150 mL min) was introduced. -1 ), 5℃min -1 The heating rate was raised to 800°C, and the temperature was maintained for 1 hour for activation treatment, and activated magnetic biochar was obtained after cooling;

[0038] (5) TiO2 co-precipitation loading: 1 kg of activated magnetic biochar obtained in step (4) was dispersed in 10 L of deionized water, ultrasonically stirred for 30 minutes, and then 1 L of 0.5 mol L -1 TiCl4 solution, continue stirring for 1 hour, then slowly add 1 mol L -1 The pH was adjusted to 7 with ammonia water, and the mixture was stirred for 2 hours to precipitate the TiO2 precursor on the surface of the biochar. The solid product was then vacuum filtered and washed with deionized water until neutral. Finally, the solid product was dried at 100 °C for 12 hours and calcined at 400 °C for 2 hours to obtain magnetic biochar loaded with titanium dioxide.

[0039] (6) Surface activation: 1 kg of the titanium dioxide-loaded magnetic biochar obtained in step (5) was added to 10 L of a 10% ammonium persulfate solution and stirred in a 60°C water bath for 2 hours. After the reaction was completed, the mixture was filtered and washed with deionized water until the filtrate was neutral. The product was then vacuum dried at 20°C for 12 hours to obtain surface-activated magnetic biochar.

[0040] (7) Graft polymerization of PNIPAM: 1 kg of surface-activated magnetic biochar was dispersed in 10 L of deionized water and ultrasonically stirred for 30 min. Then, 2 kg of N-isopropylacrylamide (NIPAM) monomer and 0.1 kg of ammonium persulfate (APS) as initiator were added to the solution under nitrogen protection and stirred evenly. The mixed solution was then heated to 70 °C and reacted for 6 h under nitrogen protection. After the reaction, it was cooled to room temperature, filtered, and washed with deionized water until no monomer remained. The product was vacuum dried at 50 °C for 12 h to obtain magnetic biochar loaded with PNIPAM.

[0041] (8) Granulation: The PNIPAM-loaded magnetic biochar obtained in step (7) was mixed with ordinary Portland cement in a mass ratio of 1:5, introduced into a disc granulator, started the granulator and set the speed to 20 rpm, and a small amount of distilled water was sprayed while rotating the granulator to gradually form wet granules. The granulation was continued for 3-6 minutes until the granules were formed and reached the desired particle size;

[0042] (9) Screening and drying: The granulated product is passed through 4 mm and 6 mm sieves to screen out biochar particles with a particle size between 4 mm and 6 mm. The screened biochar particles are naturally air-dried at room temperature for 48 hours. After they are hardened and dried, their quality is monitored to ensure that the required compressive strength and physical properties are achieved, and biochar particles that can repair water bodies contaminated by various heavy metals are obtained;

[0043] (10) Recycling of materials after use: Use magnetic separation or screening methods to recover biochar particles that have adsorbed heavy metals from treated water bodies. Magnetic separation can use the magnetic properties of biochar to quickly separate particles from water bodies. Screening is suitable for treating larger water bodies or flowing water bodies.

[0044] 2. Preparation steps of control group (BC):

[0045] (1) Biomass pretreatment: The recycled agricultural waste is washed to remove dirt and impurities, then cut into small pieces of 1-2 cm, placed in an oven and dried at 60°C to constant weight to obtain dry biomass;

[0046] (2) Conventional pyrolysis: The dried biomass obtained in step (1) was placed in a porcelain crucible in a muffle furnace and evenly spread. The porcelain crucible was placed in a tube furnace and high-purity nitrogen (flow rate 100 mL min -1 ) for protection, at 20℃min -1 The heating rate was raised to 400°C and pyrolyzed at 400°C for 120 min. After the muffle furnace was naturally cooled to room temperature, the pyrolysis product was taken out, the obtained biochar was ground and passed through a 100-mesh sieve to obtain uniform raw biochar powder (BC);

[0047] 2. Adsorption performance test

[0048] 1. Experimental conditions

[0049] Dosage: 1g L-1

[0050] Initial pH of solution: 5

[0051] Initial heavy metal concentration: 10 mg L-1 (10 ppm)

[0052] Heavy metal type: Pb 2+ , Cu 2+ 、Zn 2+ 、Cd 2+ 、Ni 2+ Cr 6+ 、As 3+ 、As 5+

[0053] Temperature: Room temperature (about 25°C)

[0054] Control group: original biochar (BC)

[0055] Experimental group: Biochar particles (SCBT@PNIPAM) prepared by the present invention that can repair water bodies polluted by various heavy metals

[0056] Stirring method: Constant temperature oscillator, speed 180rpm, time 24h

[0057] 2. Experimental Methods

[0058] (1) Solution preparation: Dissolve each heavy metal salt (such as Pb(NO3)2, CuSO4·5H2O, ZnSO4·7H2O, Cd(NO3)2·4H2O, NiSO4·6H2O, K2Cr2O7, As2O3, Na2HAsO4·7H2O) in deionized water to prepare a 10 mg / L heavy metal ion solution and adjust the pH to 5.

[0059] (2) Adsorption experiment: A certain amount of biochar (control group and experimental group) was added to a solution containing different heavy metal ions at a dosage of 1 g L-1, with a solution volume of 100 mL. The sample was placed in a constant temperature oscillator and oscillated at 25 °C and 180 rpm for 24 h.

[0060] (3) Separation and determination: After adsorption, filter using a 0.45 μm filter membrane and take the filtrate to determine the heavy metal ion concentration. 2+ , Cu 2+ 、Zn 2+ 、Cd 2+ 、Ni 2+The concentration of metal ions was determined by atomic absorption spectrophotometer (AAS); Cr 6+ The concentration was measured by UV-Vis spectrophotometer at 540 nm (diphenylcarbazide method); As 3+ 、As 5+ The concentration was measured by atomic fluorescence spectrophotometer (AFS).

[0061] (4) Calculation of removal rate: Based on the initial concentration and equilibrium concentration, the removal rate of heavy metal ions is calculated using the following formula:

[0062]

[0063] in:

[0064] C0: Concentration of substance before treatment (initial concentration)

[0065] Ce: concentration of substance after treatment (equilibrium concentration)

[0066] 3. Experimental results

[0067] Table 1 shows the removal rates of different heavy metal ions by the control group (BC) and the experimental group (SCBT)

[0068]

[0069] 3. Physical properties test of biochar particles

[0070] 1. Compressive strength test

[0071] 1.1 Experimental Purpose

[0072] The compressive strength of the biochar particles (SCBT) prepared by the present invention before and after use was evaluated, and the physical strength and stability in a water environment were investigated.

[0073] 1.2 Experimental methods

[0074] (1) Sample preparation

[0075] SCBT sample: biochar particles obtained according to the preparation method, with a particle size of 4-5 mm.

[0076] Control group: particles prepared from ordinary Portland cement (OPC) only, with the same particle size.

[0077] (2) Soaking treatment

[0078] Some samples were immersed in deionized water at room temperature for 72 hours to simulate the usage in actual water environment.

[0079] Another portion of the samples was kept dry as a non-soaked control.

[0080] (3) Compressive strength test

[0081] An electronic universal testing machine was used to test the compressive strength of the samples before and after immersion.

[0082] At least 5 parallel samples were tested for each group of samples, and the average value was taken.

[0083] 1.3 Experimental Results

[0084] Table 2. Compressive strength of biochar pellets (SCBT) before and after use

[0085]

[0086]

[0087] 4. Temperature responsiveness test

[0088] 1. Purpose of the experiment

[0089] The desorption performance of SCBT@PNIPAM for cationic and anionic heavy metal ions was evaluated at different temperatures and with different desorbents to verify its temperature responsiveness and reproducibility.

[0090] 2. Experimental Methods

[0091] (1) Desorbent selection

[0092] Cationic heavy metal ions (Pb 2+ , Cu 2+ 、Zn 2+ 、Cd 2+ 、Ni 2+ ):

[0093] Desorbent: 0.2mol L-1 HCl+CaCl2 mixed solution

[0094] Anion Heavy Metal Ion (Cr 6+ 、As 3+ 、As 5+ ):

[0095] Desorbent: 0.1 mol L-1 NaOH solution

[0096] (2) Temperature setting

[0097] 25℃、35℃、45℃、55℃

[0098] (3) Desorption experiment

[0099] The adsorption-saturated SCBT@PNIPAM sample was added to the corresponding desorbent with a solid-liquid ratio of 1 g L-1.

[0100] At the set temperature, shaking at 90 rpm, the desorption time was 2 hours.

[0101] Take samples to determine the concentration of heavy metal ions in the desorption solution and calculate the desorption rate.

[0102] 3. Experimental results

[0103] Table 3. Desorption rate of cationic heavy metal ions

[0104]

[0105] Table 4. Desorption rate of anionic heavy metal ions

[0106]

[0107]

[0108] 4. Results Analysis

[0109] (1) The effect of temperature on the desorption rate is significant: the desorption rate increases significantly with increasing temperature, especially above the LCST of PNIPAM (32°C), the desorption rate increases more significantly.

[0110] (2) Effective selection of desorbents: Different desorbents were selected for cationic and anionic heavy metal ions, achieving good desorption effects.

[0111] (3) At 55 °C, the desorption rate of most heavy metals reached more than 85%, proving the effectiveness of temperature-controlled desorption.

[0112] 5. Recycling performance of biochar particles

[0113] 1. Purpose of the experiment

[0114] The adsorption capacity and regeneration rate of SCBT@PNIPAM for various heavy metal ions (Pb2+, Cu2+, Zn2+, Cd2+, Ni2+, Cr6+, As3+, As5+) in multiple adsorption-desorption cycles at 55°C were evaluated to verify its regenerativeness and stability.

[0115] 2. Experimental methods

[0116] (1) Sample preparation

[0117] SCBT@PNIPAM: Prepared thermosensitive magnetic biochar particles with a particle size of 4-5 mm.

[0118] (2) Recycling method

[0119] Magnetic separation: A permanent magnet with a surface magnetic flux density of 192.11 mT is used to magnetically recover the used SCBT.

[0120] Screening and recovery: SCBT with a particle size of 4-5 mm is physically screened and recovered through an appropriate sieve.

[0121] (3) Adsorption-desorption cycle experiment

[0122] Adsorption steps:

[0123] Solution preparation: Prepare heavy metal ion solutions with an initial concentration of 100 mg L-1, including Pb2+, Cu2+, Zn2+, Cd2+, Ni2+, Cr6+, As3+, and As5+.

[0124] Dosage: SCBT@PNIPAM was added to each heavy metal solution at a dosage of 1 g L-1, and the solution volume was 100 mL.

[0125] Adsorption conditions: at 25 °C (below the LCST of PNIPAM), shaking at 180 rpm for 24 h to complete the adsorption process.

[0126] Separation and determination: The biochar particles were recovered using a magnetic separation method, the concentration of residual heavy metal ions in the solution was determined, and the adsorption capacity was calculated.

[0127] Desorption steps:

[0128] Desorbent selection: Cationic heavy metal ions (Pb2+, Cu2+, Zn2+, Cd2+, Ni2+): Use 0.2 mol L-1 HCl+CaCl2 mixed solution as desorbent.

[0129] Anionic heavy metal ions (Cr6+, As3+, As5+): Use 0.1 mol L-1 NaOH solution as desorbent.

[0130] Desorption conditions: The adsorbed SCBT@PNIPAM was added to the corresponding desorbent and shaken at 90 rpm for 2 h at 55 °C (higher than the LCST of PNIPAM).

[0131] Separation and determination: Separate the biochar particles, determine the concentration of heavy metal ions in the desorption solution, and calculate the desorption rate.

[0132] · Number of cycles: Repeat the above adsorption-desorption process for a total of three cycles.

[0133] 3. Experimental results

[0134] (1) Recovery rate data

[0135] Table 5. Recovery rate of SCBT in multiple cycles:

[0136] Cycle times 0 1 2 3 Recovery rate (%) 100 97.6 95.4 94.9

[0137] (2) Adsorption capacity and regeneration rate of heavy metal ions

[0138] Table 6. Adsorption capacity and regeneration rate of SCBT@PNIPAM for heavy metal ions in the cycle

[0139]

[0140]

[0141] 4. Results Analysis

[0142] (1) Recovery performance analysis

[0143] High recycling rate: The recycling rate after the first use was 97.6%, and after three cycles the recycling rate remained above 94.9%, indicating that SCBT has good recycling performance.

[0144] Quality loss: During the recycling process, there may be slight wear and tear on the surface of biochar particles, resulting in a slight decrease in quality and recovery rate.

[0145] Magnetic retention: After three cycles, the magnetism of SCBT only decreased by about 3%, and the magnetism remained basically stable, and it can still be effectively separated and recovered.

[0146] (2) Magnetic properties retention

[0147] Magnetic field strength requirements: Experiments show that when the magnetic field flux density B>5.44mT, the SCBT can still be effectively attracted by the magnet after three cycles of use to achieve magnetic separation.

[0148] (3) Regeneration ability:

[0149] Pb2+ and Cd2+ have the highest adsorption capacity and high regeneration rate after desorption, making them suitable for repeated use.

[0150] Although the removal rates of As3+ and As5+ are high at low concentrations, their adsorption capacity is limited at high concentrations, and the regeneration rate decreases significantly after desorption, so the desorption conditions need to be optimized.

[0151] The adsorption capacity and regeneration rate of Ni2+ and Cr6+ were both low, which may be due to their weak affinity with the material or difficulty in desorption.

[0152] The adsorption performance of heavy metal ions that are difficult to desorb decreases more significantly during the circulation process, and it is necessary to adjust the type or concentration of the desorbent, or extend the desorption time.

[0153] (4)Material stability:

[0154] Although the regeneration rate of some heavy metal ions decreased, the overall performance of SCBT@PNIPAM was stable during recycling and had practical application value.

[0155] (5) Practicality: The magnetic separation method is fast and efficient, does not require filtration or centrifugation, and is suitable for large-scale water treatment applications.

Claims

1. A method for preparing biochar particles that can repair water bodies polluted by multiple heavy metals, characterized in that: The following steps are involved: (1) Biomass pretreatment: The recycled agricultural waste is washed to remove dirt and impurities, then cut into small pieces of 1-2 cm, placed in an oven and dried at 60°C to constant weight to obtain dry biomass; (2) Iron salt impregnation: Weigh 1 kg of the dried biomass obtained in step (1) and immerse it in 20 liters of 0.1 mol / L -1 Fe 3+ The solution was then added with oxalic acid dihydrate and then 1 mol L -1 The pH value was adjusted to 6-7 by using NaOH solution, and then the mixture was stirred continuously for 3 h in a water bath at 90 °C, covered with plastic wrap, reacted for 24 h, and the solid product was collected by vacuum filtration and washed with deionized water until the filtrate was neutral. Finally, the solid product was vacuum dried at 50 °C for 24 h to obtain dry iron-loaded biomass. (3) Pyrolysis: The dried iron-loaded biomass obtained in step (2) is placed in a quartz crucible of a microwave pyrolysis furnace, evenly spread, and high-purity nitrogen is introduced at the same time. The temperature is then raised to 400°C at 20°C min-1, and the pyrolysis is maintained at 400°C for 120 min. The temperature is then naturally lowered to obtain a pyrolysis product. The obtained biochar is then ground and passed through a 100-mesh sieve to obtain a uniform biochar powder. (4) CO2 activation: The biochar powder obtained in step (3) was placed in a quartz boat in a tube furnace, evenly spread, and then high-purity carbon dioxide gas (flow rate of 150 mL min) was introduced. -1 ), 5℃min -1 The heating rate was raised to 800°C, and the temperature was maintained for 1 hour for activation treatment, and activated magnetic biochar was obtained after cooling; (5) TiO2 co-precipitation loading: 1 kg of activated magnetic biochar obtained in step (4) was dispersed in 10 L of deionized water, ultrasonically stirred for 30 minutes, and then 1 L of 0.5 mol L -1 TiCl4 solution, continue stirring for 1 hour, then slowly add 1 molL -1 The pH was adjusted to 7 with ammonia water, and the mixture was stirred for 2 hours to precipitate the TiO2 precursor on the surface of the biochar. The solid product was then vacuum filtered and washed with deionized water until neutral. Finally, the solid product was dried at 100 °C for 12 hours and calcined at 400 °C for 2 hours to obtain magnetic biochar loaded with titanium dioxide. (6) Surface activation: 1 kg of the titanium dioxide-loaded magnetic biochar obtained in step (5) was added to 10 L of a 10% ammonium persulfate solution, and stirred in a 60° C. water bath for 2 hours. After the reaction was completed, the mixture was filtered and washed with deionized water until the filtrate was neutral. The obtained product was then vacuum dried at 20° C. for 12 hours to obtain surface-activated magnetic biochar. (7) Graft polymerization of PNIPAM: 1 kg of surface-activated magnetic biochar was dispersed in 10 L of deionized water and ultrasonically stirred for 30 min. Then, under nitrogen protection, an initiator was added to the solution and stirred evenly. The mixed solution was then heated to 70 °C and reacted under nitrogen protection for 6 h. After the reaction was completed, it was cooled to room temperature, filtered, and washed with deionized water until no monomer remained. The product was vacuum dried at 20 °C for 12 h to obtain magnetic biochar loaded with PNIPAM. (8) Granulation: The PNIPAM-loaded magnetic biochar obtained in step (7) was mixed with ordinary Portland cement in a mass ratio of 1:5, introduced into a disc granulator, started the granulator and set the speed to 20 rpm, and a small amount of distilled water was sprayed while rotating the granulator to gradually form wet granules. The granulation was continued for 3-6 minutes until the granules were formed and reached the desired particle size; (9) Screening and drying: The granulated product is passed through 4 mm and 6 mm sieves to screen out biochar particles with a particle size between 4 mm and 6 mm. The screened biochar particles are naturally air-dried at room temperature for 48 hours. After they are hardened and dried, their quality is monitored to ensure that the required compressive strength and physical properties are achieved, and biochar particles that can repair water bodies contaminated by various heavy metals are obtained; (10) Recovery of materials after use: Using magnetic separation or screening methods, biochar particles adsorbing heavy metals are recovered from treated water bodies; (11) Temperature-controlled desorption: The recovered biochar particles are placed at an appropriate desorption temperature and treated under stirring conditions for 2 hours. After the desorption is completed, the biochar particles and the desorption liquid are separated by filtration; (12) Recycling of biochar particles: The desorbed biochar particles were washed with deionized water until neutral, and vacuum dried at 50°C for 12 hours to obtain dried biochar particles.

2. The method for preparing biochar particles capable of repairing water bodies polluted by multiple heavy metals according to claim 1, characterized in that: In step (2), the amount of oxalic acid dihydrate is Fe 3+ 50% of the molar amount.

3. The method for preparing biochar particles capable of repairing water bodies polluted by multiple heavy metals according to claim 1, characterized in that: In step (7), the initiator is a mixture of N-isopropylacrylamide monomer and ammonium persulfate, wherein the added amount of N-isopropylacrylamide monomer is 2 kg, and the added amount of ammonium persulfate is 0.1 kg.

4. The method for preparing biochar particles capable of repairing water bodies polluted by multiple heavy metals according to claim 1, characterized in that: The magnetic separation in step (10) can utilize the magnetic properties of biochar to quickly separate particles from the water body; screening is suitable for treating larger water bodies or flowing water bodies.

5. The method for preparing biochar particles capable of repairing water bodies polluted by multiple heavy metals according to claim 1, characterized in that: The decomposition temperature is 40-60°C.

Citation Information

Cited By

  • Heavy metal pollution repair material based on waste high-molecular polymer and inorganic mineral powder as well as preparation method and application of heavy metal pollution repair material

    CN121244645A